Telecommuting and environmental policy - lessons from the Ecommute program - Margaret Walls; Peter Nelson; Elena Safirova (European Regional Science Association (ERSA), 2005)
In 1999 US Congress passed the National Air Quality and Telecommuting Act. This Act established pilot telecommuting programs (Ecommute) in five major US metropolitan areas with the express purpose of studying the feasibility of addressing air quality concerns through telecommuting. The major goal of the Ecommute program was to examine whether a particular type of economic incentive, tradable emissions credits from telecommuting, represents a viable strategy for reducing vehicle miles traveled (VMT) and improving air quality. Under the Ecommute program, companies could generate emissions credits by reducing the VMT of their workforce through telework programs. They would then be able to sell the credits to firms that needed the reductions to comply with air quality regulations. The paper provides analysis of the results of Ecommute program. First, we establish some context for evaluating whether the envisioned trading scheme represents a feasible approach to reducing mobile source emissions and promoting telecommuting and review the limited experience with mobile source emissions trading programs. We find that from a regulatory perspective, the most substantial drawback to such a program is its questionable environmental integrity, resulting from difficulties in designing a sufficiently rigorous quantification protocols to accurately measure the emissions reductions from telecommuting. And perhaps more importantly, such a program is not likely to be cost-effective since the emissions reductions from a single telecommuter are very small. The paper also presents the first analysis of data collected from the Ecommute program. Using two-and-one-half years of data, we look at telecommuting frequency, mode choice, and emissions reductions as well as at reporting behavior and dropout rates. Finally, we use the program's emissions reductions findings to calculate how much telecommuting would be needed to reach an annual volatile organic compounds emission reduction target in each city.
Keywords: 330